PENGARUH TERAPI MUSIK PADA PASIEN KANKER PARU DENGAN NYERI KRONIK - Dedeh Komalawati (Afiat, 2021)
Lung cancer is an epithelial cell mutation caused by carcinogens and is influenced by genetic factors. Complaints that often appear are cough, hemoptysis, dyspnea, hoarseness, superior vena cava syndrome, pleural effusion, pancoast tumor and chest pain. Pain management is needed by lung cancer patients both pharmacologically and non-pharmacologically. One of the non-pharmacological pain management is music therapy. The purpose of this study was to determine the effect of music therapy on lung cancer patients with chronic pain. The research design used was quasi-experimental with non-equivalent pretest-posttest with control group, consecutive sampling was used as the sample. The number of samples was 36 people (18 control group and 18 intervention group). Pain was measured by a numerical rating scale. The statistical test used a two-mean difference test. The results showed that there was a significant effect of music therapy on lung cancer patients with chronic pain (p value = 0.000; = 0.05). The results of this study recommend music therapy as an independent nursing intervention to reduce chronic pain in lung cancer patients.